The Role of Dipeptide Repeats in C9ORF72-Related ALS-FTD - Freibaum, Brian D.; Taylor, J. Paul (Frontiers in Molecular Neuroscience, 2017)
Expansion of a hexanucleotide (GGGGCC) repeat in the gene C9ORF72 is the most common cause of amyotrophic lateral sclerosis and frontotemporal dementia. Three non-exclusive mechanisms have been proposed to contribute to the pathology initiated by this genetic insult. First, it was suggested that decreased expression of the C9orf72 protein product may contribute to disease. Second, the recognition that C9ORF7¬2-related disease is associated with accumulation of GGGGCC repeat-containing RNA in nuclear foci led to the suggestion that toxic gain of RNA function, perhaps related to sequestration of RNA-binding proteins, might be an important driver of disease. Third, it was subsequently appreciated that GGGGCC repeat-containing RNA undergoes unconventional translation to produce unnatural dipeptide repeat proteins that accumulate in patient brain early in disease. Dipeptide repeats translated from all six reading frames in either the sense or antisense direction of the hexanucleotide repeat result in the expression of five dipeptide repeats: glycine–alanine, glycine–arginine, proline–alanine, proline–arginine, and glycine–proline (glycine–proline is generated from both the sense and antisense reading frames). However, the relative contribution of each dipeptide repeat to disease pathogenesis remains unclear. Here, we review evidence for the contribution of each specific dipeptide repeat to pathogenesis and examine the probable mechanisms through which these dipeptide repeats induce neurodegeneration. We also consider the association of the toxic dipeptide repeats with impaired RNA metabolism and alterations to the liquid-like state of non–membrane-bound organelles. .